MORPHOGENESIS FEATURES OF THE URETEROPELVIC JUNCTION IN HUMAN FETUSES AND NEWBORNS - Tsyhykalo, O.V.; Oliinyk, I.Yu.; Andrushchak, L.A.; Галиш, І.В. (World of Medicine and Biology, 2020)
The purpose of the study was to find out the features of the ureteropelvic junction structure in the fetal period of ontogeny and in newborns, and to determine the critical periods of its morphogenesis. The study was performed on 67 human fetal specimens with 160.0-500.0 mm of parietococcygeal length (PCL) (4th-10th months of prenatal development). A set of morphological study methods was applied, which included anthropometry, morphometry, injection of vessels with their subsequent radiography and preparation, microscopy, graphic and three-dimensional computer reconstruction, statistical analysis. It is established that the size of the ureteropelvic junction in the early period of ontogeny increases asynchronously: during the 4th month its length increases, during the 7th month and in newborns its diameter grows. From the 4th month of intrauterine development up to the newborn period the ureteropelvic junction’s diameter increases from 0.95±0.25 mm to 2.2±0.25 mm. At the beginning of the fetal period (4-5 months), the ureteropelvic junctions are determined at the level of the intervertebral interval between II and III lumbar vertebrae. During the second half of the fetal period, its asymmetrical shift occurs: to the left - to level II, and to the right - to level III of the lumbar vertebrae. In the perinatal period of ontogenesis, close anatomical correlations of the ureteropelvic junction with the renal vessels are determined - its anterior surface is crossed by 2-4 branches of the renal artery and 2-3 branches of the renal vein.
Keywords: ureteropelvic junction; anatomy; fetus; newborn